Effectiveness of Wobble Board Exercises on Dynamic Balance among Undergraduate Students - Ushna Yalnaz; Usman Sarwar; Sumair Quresh; Hafiz Sulman Saeed; Imran Manzoor; Nusrat Rasheed (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE:  Control of posture and balance is vital in mobility. Board exercise provides information about the motor strategies associated with muscle activation patterns that result when a person is standing on a wobble board surface that unexpectedly translates or tilts, which stimulates proprioception on the ankle.METHODOLOGY: This study recruited 37 Undergraduate medical students of Allied health sciences (including males and females) of age between 17 to 25 years, conducted at skill lab of Shalamar Institute of Health Sciences. It is a Pre-test, Post-test Quasi-Experimental study in which balance was assessed by performing SEBT while maintaining single-limb stance. After 2 weeks of training, a dynamic balance was reassessed using Star Excursion Balance Test (SEBT).RESULTS: A total of 37 patients are included in this study with the age of 22.0±1.65 years and BMI 20.9±3.02 are considered. The study includes 15 male and 22 female patients. This study shows significant differences in Pre-SEBT and Post-SEBT values of legs as p-value <0.05.CONCLUSION: There were significant differences in Pre-exercising and Post-exercising SEBT. Study shows that wobble board-based rehabilitation training has a positive impact on improving balance of participants.